OVERVIEW OF THE IMPLEMENTATION OF ENVIRONMENTAL EDUCATION IN WILDLIFE CONSERVATION EFFORTS AT 003 LUBUK KEMBANG ELEMENTARY SCHOOL, LOCATED IN THE BUFFER ZONE OF TESSO NILO NATIONAL PARK, RIAU PROVINCE - Fani, Rifia Tiara; Restilla, Ridha; Suprayoga, Tito; Putri, Frilianty; Saukhan, Ghiandra N.S.; Pratiwi, Nurfi; Nurkasanah, Siti; Anggraini, Dewi; Nurfadila,; Hanifah, Zulfa Nur; Namira, Syafira Nihla (Buletin Veteriner Udayana, 2026)
Indonesia, as a mega-biodiversity country, faces huge pressure on its ecosystems and wildlife due to deforestation, exploitation of natural resources, and low environmental literacy among the community, including in the buffer zones of national parks. Environmental education from an early age is an important strategy in building conservation awareness and pro-environmental behavior. This study aims to describe the implementation of environmental education in wildlife protection efforts in elementary schools located in the buffer zone of Tesso Nilo National Park, Riau Province. This study uses a descriptive approach with quantitative and qualitative methods. A total of 50 students aged 8–12 years were selected using purposive sampling to complete a conservation understanding questionnaire, while in-depth interviews were conducted with two teachers. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed thematically. The results showed that the students' initial level of understanding of wildlife conservation was still relatively low, with an average score of 60.3 ± 15.1. Environmental education in schools has been integrated into the 2013 Curriculum, but it does not specifically include material on wildlife conservation and forest preservation, nor is it supported by ongoing external education programs. The results of the study show that students' initial level of understanding of wildlife conservation is still relatively low, with an average score of 60.3 ± 15.1. Environmental education in schools has been integrated into the 2013 Curriculum, but it does not specifically include material on wildlife conservation and forest preservation, nor is it supported by ongoing external education programs. The results of this study indicate that the implementation of environmental education in the buffer zone of Tesso Nilo National Park is still not optimal in building a comprehensive understanding of wildlife conservation. There is a need to strengthen conservation-based environmental education through curriculum integration, the development of contextual educational media, and the implementation of sustainable and participatory non-formal education programs.